EFFECTIVENESS OF PARETO (ABC) ANALYSIS IN PHARMACEUTICAL INVENTORY PLANNING AT COMMUNITY PHARMACIES A NARRATIVE REVIEW - Yunita Handoyo, Diana Lady (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
Inventory planning is a crucial component of community pharmacy practice, as it plays an important role in ensuring medicine availability while maintaining cost efficiency. One commonly applied method in inventory management is Pareto Analysis (ABC), which classifies pharmaceutical items based on their contribution to the total inventory value. This review article aims to evaluate the effectiveness of implementing ABC analysis in pharmaceutical inventory planning in community pharmacies by examining its conceptual foundations, practical benefits, and limitations. A narrative review method was employed by analyzing reputable scientific literature addressing inventory management, ABC analysis, and its application in pharmacy and healthcare services. The findings indicate that ABC analysis is effective in prioritizing the control of high-value medicines, improving procurement efficiency, and reducing the risks of stockouts and overstocking. However, the strong emphasis on economic value requires adaptive implementation to ensure that the method remains clinically relevant and aligned with patient safety considerations